Effects of Exercise on Hormones in Women with Polycystic Ovary Syndrome - Gaisamudre (Sarwade), Kavita Narayan; Sarwade, Sarika Pralhad; Sarwade, Prakash Pralhad; Singh, Deeksha; Srinandhinidevi, K. M.; Rani, M. Jansi; Kavita, Jadhav; Chirmade, Dipti Hitendra (Journal for Research in Applied Sciences and Biotechnology, 2024)
Numerous reproductive-aged women are impacted by polycystic ovary syndrome (PCOS), an endocrine-gynecology condition. While a risk factor for polycystic ovarian syndrome (PCOS) has been identified, much about the disease's origins and pathophysiology is still up in the air. We searched PubMed and ClinicalTrials.gov extensively for results pertaining to the utilisation of repurposed pharmaceuticals in order to acquire information about the causes and treatments of polycystic ovarian syndrome (PCOS) for this study. We looked at everything that could be causing polycystic ovary syndrome. In addition, the data for both the most commonly prescribed PCOS medications and those that have been repurposed are summarised in the tables. Insulin resistance, inflammation, environmental toxicants, epigenetics, oxidative stress, hyperandrogenism, stress, and nutrition were all part of the internal components that were reviewed. Altering one's way of life and making use of complementary and alternative medicine is often the first line of defence against illness for many people. There is some evidence that certain medications and supplements may be effective in treating polycystic ovarian syndrome (PCOS). These chemicals include mucolytic medicines, thiazolidinediones, sodium-glucose cotransporter-2 inhibitors, dipeptidyl peptidase-4 inhibitors, 3-hydroxy-3-methyl-3-glutaryl-coenzyme A (HMG-CoA) reductase inhibitors, and glucose-like peptide-1 receptor agonists.